1834. Evaluation of De-Escalation Options after Combination Daptomycin and Ceftaroline Therapy for Persistent MRSA Bacteremia. (15th December 2022) - Carroll, Ryan D; Brown, Matthew L; Edwards, William S; Stripling, Joshua
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) bacteremia carries high mortality with limited treatment options. Studies over the last decade support glycolipopeptide and beta-lactam combination therapy with daptomycin (DAP) and ceftaroline (CFT) combination gaining prominence. While data supports de-escalation to monotherapy after bacteremia clearance it does not guide the choice of agent. With barriers including accessibility, cost, and tolerability of these agents, data is needed to optimize treatment. This study aims to evaluate de-escalation options after combination DAP/CFT therapy for persistent MRSA bacteremia. Methods: A single-center, retrospective review of cases of persistent MRSA bacteremia (defined as greater than 72 hours on appropriate therapy) requiring escalation to DAP/CFT between 2014 and 2021 was performed. Details of bacteremia, source of infection, and comorbidities were assessed, and outcomes including recurrence of infection, infection-associated mortality, and tolerability were compared using exact Chi-square testing and univariant analysis. Results: Sixty-six cases were identified of which 7 were de-escalated to vancomycin (VAN), 48 to DAP, 4 to CFT, and 7 continued DAP/CFT combination. Demographics and details of bacteremia such as prior anti-MRSA therapy, duration prior to DAP/CFT therapy, and source identification were similar between groups. Differences included higher rates of hemodialysis patients in the VAN group, higher rates of immunocompromised hosts in the DAP group, higher average Pitt bacteremia score in the DAP/CFT group, and lower rates of source control in the VAN group. Recurrence of infection (29% VAN, 13% DAP, 25% CFT) and infection-related mortality (14% VAN, 8% DAP) were higher in the VAN group (p=0.0452). In the DAP group 23% required change in therapy during their course. Univariant analysis assessing for confounding from comorbidities and source control yielded no significant associations. Conclusion: This study is limited by small, uneven sample sizes but the results identify a trend of increased recurrence rates and mortality with de-escalation to VAN but tolerability concerns with DAP. More study is needed to guide clinical care and this data provides framework for future research. Disclosures: All Authors : No reported disclosures.